The effect of using different types of polar solvents on the percentage of yield and gallic acid in the piper betel leaves extract / Nurul Nadiha Othman - Othman, Nurul Nadiha (2023)
The piper betel is a dioecious, evergreen vine with glossy, heart-shaped leaves and white catkins. Piper betel leaves are extracted from various parts of plants and are widely used in various fields of industry, such as medicine, cosmetics, food stuffs, and the pharmaceutical industry. The antioxidant activity of most of the plants produced is mainly due to the presence of bioactive compounds. Until now, a wide variety of bioactive substances from betel leaf extracts and essential oils (EO), such as polyphenols and terpenes, have been found. The solvent used in the extraction process is crucial to extract its bioactive compound which contribute to its therapeutic activities. However, the effects of various solvents on the antioxidant and antibacterial activity of piper betel leaf extract have not been well studied. Therefore, the objective of this study is to determine the effect of different extraction solvents on piper betel leaves using a soxhlet apparatus. The extraction of piper betel leaf was done by using Soxhlet extraction technique and the determination and quantification of Gallic acid was implemented by using High Performance Liquid Chromatography (HPLC). From the result, the aqueous extract has the higher percentage of yield, which is 23.33%, and the methanol has the lower percentage of yield, which is 16.67%. According to the findings, extraction in highly polar solvents resulted in a high extract yield. In addition, the polarity of the solvent affects the efficiency of the extraction, total phenolic content, and antioxidant activity of the obtained extracts. Furthermore, further examination of the HPLC analysis revealed the presence of garlic acid in the piper betel leaf extract. From the HPLC chromatogram result, the methanol extracts (32.51 ppm) contain the highest concentration of Gallic acid compared to the other solvents used for the extraction process. This result indicates that methanol solvent is a better extraction solvent compared to other solvents for the extraction of Gallic acid from the piper betel leaves extracts.